Increasing Student Proactivity Through Entrepreneurship Education (A Studi Systematic Literature Review) - Fauzi, Khoiron; Jaelani, Meta Humaira; Wati, Andy Prasetyo; Murwani, F. Danardana; Wardana, Ludi Wishnu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The systematic literature review article on increasing student proactivity through entrepreneurship education aims to highlight the importance of entrepreneurship education in developing students' proactive attitudes. Entrepreneurship education can improve students' skills and interest in starting and managing a business in the future. The method used in writing systematic literature review (SLR) articles is a library research method. Bibliographic sources come from Scopus, ProQuest, and Springer Link databases. The results of the analysis of relevant articles found that proactivity developed in entrepreneurship education helps students increase entrepreneurial intentions, entrepreneurial actions, and innovation in entrepreneurship. These three competencies shape students to create new markets with high value and promote products and services at low costs.